(untitled) (Journal of Asian Development Studies, 2024)
Thalassemia is a chronic, life-threatening genetic blood disorder that has numerous socio-economic and health impacts on patients, caregivers and families globally. The issue of thalassemia is rapidly increasing among infants and children, and a large proportion of the affected population is living in developing countries like Pakistan. The patients suffering from thechronic issue bear symptoms such as pale skin, weakness, shortness of breath and jaundice. Thalassemia has severe complications with long-lasting consequences on the patients as well as their caregivers. Limited health care services, lack of social support, misconceptions about the condition, the stigma and discrimination within their families and communities can lead to disruption of their physical, cognitive, social and economic conditions. Several coping mechanisms are applied to deal with discomfort that could manage stress-related demandsthat arisedue to environmental transactions that eventually exceed personal resources. The present study examined the psycho-social challenges faced by caregivers of thalassemia patients and identified the coping strategies employed by these caregivers in Gujrat city. Researchers used the purposive sampling technique for this quantitative study to collect primary data through a structured questionnaire. The findings highlighted that the caregivers of thalassemia patients face various psychological challenges such as depression, fear of losing a loved one life, and feelings of isolation. This can negatively impact the overall well-being of the caregiver. Additionally, they face social challenges, including social stigma and limitations in maintaining social connections